SELF - AWARENESS AND PREVENTION BEHAVIOR PROGRAM OF COVID - 19 USING REASONED ACTION THEORY AND SOCIAL INTELLIGENCE LEARNING THEORY OF SECONDARY SCHOOL STUDENTS - Kongsuwan, Anon; Sarayuthpitak, Jintana; Rodpipat, Sarinya (Academic Journal of Thailand National Sports University, 2023)
Purposes: To compare mean scores of self-awareness and prevention behavior of Covid - 19 after implementation between the experimental group and the control group. Methods: The samples were 40 secondary school students and were divided into two groups each group 20. The research instruments consisted of 7 activities: 1. Self - assessment, 2. Information recognition, 3. Practice, 4. Reinforce and Suggest, 5. My idol, 6. Consult, and 7. Student Leader with IOC of 0.98 and the data collection instruments included self-awareness and prevention behavior test with IOC of 0.99 and 0.95 reliabilities of 0.84 and 0.82, and discrimination of 0.26 – 0.69 and 0.31 – 0.69. The duration of the experiment was 8 weeks. The data were analyzed by mean, standard deviation, and t - test (paired - Sample t - test, independent sample t - test). Results: The research finding was as follows: The mean scores of self - awareness and prevention behavior of Covid-19 of the experimental group students after the assigned program were significantly higher than before the assigned program at a .05 level, and the mean scores of self - awareness are higher than that in the control group students at .05 level. Conclusion: Self - awareness and prevention behavior program of COVID - 19 using reasoned action theory and social intelligence learning theory of secondary school can improve self -awareness and prevention behavior in secondary school.